Stepwise response-guided treatment protocol superior to thrombopoietin receptor agonist-based second-line therapy for severe persistent/chronic immune thrombocytopenia: a multicenter prospective study from China - Lingling Fu; Xi Lin; Zhenping Chen; Zhifa Wang; Yan Liu; Lijuan Wang; Yu Hu; Jingyao Ma; Nan Wang; Xiaoling Cheng; Jie Ma; Runhui Wu (Research and Practice in Thrombosis and Haemostasis)
Background: The first second-line international recommendation for children with severe persistent/chronic immune thrombocytopenia is thrombopoietin receptor agonist (TPO-RA)-based treatment; however, <30% can achieve sustained response off-treatment (SRoT), leading to a heavy medical burden. Objectives: This study aimed to confirm the efficacy of the stepwise response-guided treatment protocol compared with TPO-RA–based second-line therapy for children with severe P/CITP. Methods: The stepwise response-guided treatment protocol is an individualized stratified immune thrombocytopenia treatment starting with high-dose dexamethasone, then adding rituximab and TPO-RAs in sequential order according to treatment response. A prospective, multicenter clinical cohort study enrolled severe P/CITP children with a 1-year follow-up. We compared the treatment outcome response of platelet count, bleeding control, and treatment-related side effects and cost outcomes (escalation status, SRoT, and treatment costs) between the stepwise group and the TPO-RA–based second-line treatment group (TPO-RA group). Results: The study enrolled 143 cases of severe P/CITP children with a 12-month follow-up period. There were no differences in baseline characteristics between the stepwise and TPO-RA groups (P > .05). Response/remission rates and bleeding grades showed no differences (P > .05), but there were fewer side effects related to treatment in the stepwise group (9.0%; P < .00). A total of 74% in the stepwise group achieved SRoT while none in the TPO-RA group did. The cost of treatment was significantly lower in the stepwise group compared with the TPO-RA group over the 12-month follow-up period (USD 68.26/kg vs USD 384.76/kg, P < .00). Conclusion: The stepwise response-guided treatment protocol effectively stratifies children with severe P/CITP based on treatment response, enabling individualized treatment strategies. This protocol achieves comparable efficacy and safety while reducing the treatment burden compared with TPO-RA–based second-line therapy, making it a preferable option for children with severe P/CITP.